A cohort study of retinal detachment among Swedish construction workers - Kevin D Schott; David Kriebel; Susan R Sama; Bryan O Buchholz; Bengt Järvholm; Jens Wahlström (Nordic Association of Occupational Safety and Health (NOROSH), 2023)
OBJECTIVE: Retinal detachment (RD) has been associated with exposure to heavy lifting. Many occupations within the construction industry are likely to involve lifting tasks. We investigated the association between occupational heavy lifting and rhegmatogenous RD in a retrospective cohort study of Swedish construction workers. METHODS: We studied Swedish construction workers who participated in an industry-wide health and safety program from 1971 to 1993. Individual occupation codes were linked to a job exposure matrix, assigning intensity of exposure to heavy lifting to each worker. The Swedish National Patient Register was used to identify cases of RD that occurred during follow-up through the end of 2012. We used Poisson regression modeling to calculate incidence rates of RD associated with heavy lifting, age and other covariates. A subcohort of those age ≤25 years at enrollment was studied to reduce bias from missing exposure information from work prior to enrollment. RESULTS: Of 256 241 construction workers, 17% were classified with high exposure to heavy lifting in their occupation. Within the cohort, 1588 cases of RD were identified. Average exposure intensity of heavy lifting was not associated with risk of RD. However, RD risk increased with increasing cumulative exposure to heavy lifting, both in the full cohort and subcohort of those who were ≤25 years old at entry into the construction-worker cohort. CONCLUSION: Construction workers' risk of RD appeared to increase with time spent exposed to heavy lifting.